Hua peopleñDescendants of the dragonñChinese : an archaeological seeking after roots - Su Bingqi
This article, first published in Zhongguo jianshe [China Reconstructs 1987(9)], became particularly well known when it was selected for the 'Language and literature paper' in the 1988 national university entrance examinations. this English version is translated and footnoted byu Wang Tao.